2010
DOI: 10.1002/prep.201000030
|View full text |Cite
|
Sign up to set email alerts
|

A Device for Testing Thermal Impact Sensitivity of High Explosives

Abstract: A drop‐weight instrument is described to investigate the impact sensitivity of high explosives at elevated temperatures. This test is typically performed to discover potential safety aspects of either newly synthesized materials of unknown behavior. Normally, drop‐weight impact sensitivity tests are conducted at room temperature, since high explosives are often stored or handled at room temperature. The instrument described here has the capability of heating the samples from ambient to 300 °C prior to impact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…[21] Measurements were conducted in the following way: hammer of adjustable weight (0.5-6.8 kg) was held by an electromagnet at a varying height (1-100 cm). Starting from the minimum weight and height the hammer was released onto the anvil with the sample (weight of sample: 25 mg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Measurements were conducted in the following way: hammer of adjustable weight (0.5-6.8 kg) was held by an electromagnet at a varying height (1-100 cm). Starting from the minimum weight and height the hammer was released onto the anvil with the sample (weight of sample: 25 mg).…”
Section: Methodsmentioning
confidence: 99%
“…Using this instrument 50 % probability of explosion for HMX was achieved at a weight of 5 kg and a height of 56 cm. [21] Comparatively, complex 2 was shown to be insensitive over the weight and height range tested. Repeated attempts to ignite either complex using the electric spark test failed to show any response, indicating that both complexes are stable to a static shock (discharge).…”
Section: Energetic Propertiesmentioning
confidence: 97%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 After being heated at 160 8C for 10 min, the impact sensitivity decreased to 49.2 cm, 36.5 cm and 29.7 cm, severally. Combining Table 2 with Table 1, it shows that the decrease in impact sensitivity of CL-20 is not only related with the increase of g phase caused by phase transition after thermal insults, which has been correlated directly with void space volume in CL-20 crystal [7,21], but also related to the particle size of heated CL-20 crystals. For the drop-weight impact, the hot spot temperature is higher for large particles with large hot spots, than for small particles with small hot spots.…”
Section: Impact Sensitivitymentioning
confidence: 92%
“…In such case, the sensitivity of the explosive would be increased significantly. For example, Zhang and Weeks performed drop-weight impact sensitivity tests for HMX at various temperatures [21]. Their results showed that as the temperature was increased above 175 8C, there is a dramatic decline of drop height which shows a good consistency with the phase transition temperature of HMX from bto g-HMX, indicating that the sensitivity of HMX increased due to the phase transition from bto g-HMX.…”
Section: Introductionmentioning
confidence: 99%
“…
1IntroductionOne of the concerns in today's workw ith energetic materials is the safety of their exposure to hight emperatures. HMX being the energeticc omponent of an umber of plastic-bonded explosives (PBX) and rocket propellant formulations, the details of its phase transition (PT) and energyr elease are of great interest [1,2].F or HMX-based PBX,t he b!d PT of HMX can occur at high temperatures;d uring this process, the crystalv olume increases by 6-7 %a nd the density decreases [1,2].T his is the main reason why heating enhances the HMX sensitivity [3][4][5][6].U nderstanding the PT and phase stability properties of this material is thusn ot only of intrinsic interest but also crucial for predicting the full energetic response of HMX-based materials underavariety of conditions.To clarify the safetyo fH MX-based PBX under high temperature and to control the PT,i ti sn ecessary to gain ad eep understanding of the PT behavior.I n2 002 Saw et al[7] studied the b!d PT dynamics of the HMX particles of variouss izes. They found that under the same heating rate, the PT temperature of largerp articlesi sl ower than thato fs maller particles, i.e.,t he PT activation energy is lower for larger particles.
…”
mentioning
confidence: 99%